Heparin Cofactor II: Purification and Antibody Production - Tran, Tri H; Lämmle, B; Zbinden, B; Duckert, F (Thrombosis and Haemostasis, 1986)
Heparin cofactor II (HCII) was purified from plasma to homogeneity. The procedure includes adsorption with (Al)OH3, fractionation with polyethylene glycol 6000, chromatography on QAE-Sephadex A-50, on heparin-Sepharose 4B and on Sephadex G-150. QAE-Sephadex A-50 chromatography provides a good separation of HCII from antithrombin III (AT) and most contaminants having a heparin affinity similar to that of HCII. HCII is eluted at 0.28 M NaCl from the heparin-Sepharose column. After gel filtration on G-150, contaminating AT was removed by immunoadsorption. Purified HCII shows an apparent Mr of 66,500 dal tons as analyzed on SDS-polyacrylamide gel and 62,100 daltons by ultracentrifugation. Antibodies to HCII were raised in rabbits. Former antisera mostly directed to a contaminating protein were used to remove it from the HCII preparation. Antibodies to HCII were made monospecific by immunoadsorption on HCII-free plasma linked to Sepharose 4B. Since many functional AT assays have neglected the presence of HCII in plasma, antibodies to HCII using as immunoadsorbent will provide a more specific test for AT.
Keywords: Heparin cofactors; Antibody specificity; Antithrombin III; Unknown protein; Fluid dynamics